Reduced expression of circRNA hsa_circ_001888 in gastric cancer and its clinical significance. Issue 9 (16th August 2021) - Shi, Peina; Song, Haojun; Ding, Xiaoyun
Abstract: Background: Circular RNAs (circRNAs) are a novel family of endogenous RNAs. Recent studies have demonstrated that circRNAs are potential novel biomarkers for diagnosing cancers. However, little is known about the role of circRNAs in gastric cancer (GC). This study aimed to identify the relationship between GC and a new circRNA named hsa_circ_001888. Methods: Hsa_circ_001888 expression levels were measured by quantitative reverse transcription‐polymerase chain reaction (qRT‐PCR) in GC cell lines, tissues, and plasma samples. Then, the associations between the expression level of hsa_circ_001888 and the clinicopathological features of patients with GC were further investigated. A receiver operating characteristic (ROC) curve was generated to evaluate the diagnostic value of hsa_circ_001888. Results: In this study, hsa_circ_001888 was first found to be significantly downregulated in GC cell lines (AGS and MKN‐45), tissues, and plasma samples compared to control samples. Clinicopathological features showed that the expression of hsa_circ_001888 in GC tissues was associated with differentiation and in GC plasma linked with serum CEA and CA19‐9 levels. The areas under the ROC curves of hsa_circ_001888 in tissues and plasma were 0.654 and 0.66, respectively. Conclusions: Hsa_circ_001888 may serve as a potential biomarker in the diagnosis of GC and may be involved in GC development. Abstract : This study aimed to identify the relationship between gastric cancer (GC) and a new circRNA named hsa_circ_001888. The results indicated that hsa_circ_001888 was significantly downregulated in GC cell lines, tissues and plasma samples compared to control samples. Hsa_circ_001888 may serve as a potential biomarker in the diagnosis of GC with high degrees of specificity, sensitivity and accuracy.